2017
DOI: 10.1007/s00406-017-0784-z
|View full text |Cite
|
Sign up to set email alerts
|

The association of childhood maltreatment with depression and anxiety is not moderated by the oxytocin receptor gene

Abstract: BackgroundThe oxytocin receptor (OXTR) gene may be involved in resilience or vulnerability towards stress, and hence in the development of stress-related disorders. There are indications that OXTR single nucleotide polymorphisms (SNPs) interact with early life stressors in predicting levels of depression and anxiety. To replicate and extend these findings, we examined whether three literature-based OXTR SNPs (rs2254298, rs53576, rs2268498) interact with childhood maltreatment in the development of clinically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 55 publications
3
23
1
1
Order By: Relevance
“…Secondly, the Val66Met and Met66Met genotypes, respectively, may have dissimilar effects (Hong et al, 2012). Nevertheless, the main effect of CM on AS determined in this study provides support for the positive association between CM, including stressful life events, and AS in adolescents (McLaughlin & Hatzenbuehler, 2009; Tollenaar, Molendijk, Penninx, Milaneschi, & Antypa, 2017), a well-established cognitive risk factor for the development of anxiety disorders and associated symptoms in youth (Hishinuma et al, 2001; McLaughlin et al, 2007; Muris et al, 2001). Furthermore, our finding adds to the well-established literature demonstrating the adverse acute and long-term effects of CM or trauma on mental health and cognition in youth and adults (De Bellis, Woolley, & Hooper, 2013; Greger, Myhre, Lydersen, & Jozefiak, 2015; Irigaray et al, 2013; Taillieu, Brownridge, Sareen, & Afifi, 2016; Teicher, Ohashi, Lowen, Polcari, & Fitzmaurice, 2015).…”
Section: Discussionsupporting
confidence: 67%
“…Secondly, the Val66Met and Met66Met genotypes, respectively, may have dissimilar effects (Hong et al, 2012). Nevertheless, the main effect of CM on AS determined in this study provides support for the positive association between CM, including stressful life events, and AS in adolescents (McLaughlin & Hatzenbuehler, 2009; Tollenaar, Molendijk, Penninx, Milaneschi, & Antypa, 2017), a well-established cognitive risk factor for the development of anxiety disorders and associated symptoms in youth (Hishinuma et al, 2001; McLaughlin et al, 2007; Muris et al, 2001). Furthermore, our finding adds to the well-established literature demonstrating the adverse acute and long-term effects of CM or trauma on mental health and cognition in youth and adults (De Bellis, Woolley, & Hooper, 2013; Greger, Myhre, Lydersen, & Jozefiak, 2015; Irigaray et al, 2013; Taillieu, Brownridge, Sareen, & Afifi, 2016; Teicher, Ohashi, Lowen, Polcari, & Fitzmaurice, 2015).…”
Section: Discussionsupporting
confidence: 67%
“…Other polymorphisms studied included OXTR rs2254298 and rs2268498, but neither Dunn et al ( 2014 ) nor Tollenaar et al ( 2017 ) found changes or association among the presence of ET or PTSD, a single nucleotide polymorphism, and the development of symptoms. In addition, Dunn et al ( 2014 ) investigated the role of rs53576 and did not find a difference between the presence of the AA allele and the AG or GG alleles as risk factors for the development of PTSD or its symptoms.…”
Section: Resultsmentioning
confidence: 98%
“…Cicchetti and Rogosch ( 2012 ) showed that the presence of ET and the AA/AG genotype was associated with increased resiliency; therefore, the presence of the AA/AG genotype appears to have a protective function. On the other hand, Tollenaar et al ( 2017 ) indicated that the OXTR53576 gene polymorphism does not interact with ET and predict risk factor and/or vulnerability toward the development of depression or anxiety. In addition, Sippel et al ( 2017 ) found that the presence of a minor allele associated with an insecure attachment style was associated with a higher prevalence of PTSD among war veterans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After several kinds of maltreatment in childhood (emotional, physical or sexual abuse; emotional or physical neglect), G-allele carriers have shown increased depressive symptoms [17,18], and conduct problems (in females only) [19] and GG carriers showed a higher risk of emotional dysregulation [20], compared to A-carriers. However, a study on adults with clinically diagnosed depression and anxiety disorders showed no interaction of rs53576 with one or more types of childhood maltreatment [21].…”
Section: Introductionmentioning
confidence: 95%